The putative small terminase from the thermophilic dsDNA bacteriophage G20C is a nine‐subunit oligomer. Issue 8 (31st July 2013) - Loredo‐Varela, Juan; Chechik, Maria; Levdikov, Vladimir M.; Abd‐El‐Aziz, Ahmad; Minakhin, Leonid; Severinov, Konstantin; Smits, Callum; Antson, Alfred A.
<x xml:space="preserve">Abstract</x> The assembly of double‐stranded DNA bacteriophages is dependent on a small terminase protein that normally plays two important roles. Firstly, the small terminase protein specifically recognizes viral DNA and recruits the large terminase protein, which makes the initial cut in the dsDNA. Secondly, once the complex of the small terminase, the large terminase and the DNA has docked to the portal protein, and DNA translocation into a preformed empty procapsid has begun, the small terminase modulates the ATPase activity of the large terminase. Here, the putative small terminase protein from the thermostable bacteriophage G20C, which infects the Gram‐negative eubacterium Thermus thermophilus, has been produced, purified and crystallized. Size‐exclusion chromatography–multi‐angle laser light scattering data indicate that the protein forms oligomers containing nine subunits. Crystals diffracting to 2.8 Å resolution have been obtained. These belonged to space group P212121, with unit‐cell parameters a = 94.31, b = 125.6, c = 162.8 Å. The self‐rotation function and Matthews coefficient calculations are consistent with the presence of a nine‐subunit oligomer in the asymmetric unit.